Philippines 2000 a vision for the nation. (Makati City Studio 5 Designs, Inc., 1996)
"Philippines 2000: A Vision for the Nation is a book of information, encouragement and inspiration. Originally conceived to be an interpretation of the vision of President Fidel V. Ramos, the book has, however, become more than a mere presentation of a Philippine President's vision and plans for his country."--Book jacket.
The Filipino people -- Cultural transformation -- A vision for the nation -- Economic take-off -- Civic responsibility -- Population -- National security -- Environment -- International relations.
Keywords: Ramos, Fidel Valdez -- 1928- -- Vision; Economic indicators -- Philippines; Philippines -- Economic policy -- 1993-.; Philippines -- Economic conditions -- 1993-.